A discussion on mass resolution in secondary ion mass spectrometry. (13th November 2019) - Li, Zhanping; Zhao, Lixia; Xiong, Bing; Fan, Runlong; Liu, Dunyi; Cha, Liangzhen
Abstract : Mass resolution is a very important parameter for mass spectrometry. It is necessary to compare the mass resolution between the newly developed TOF‐SIMS and the conventionally high‐performance magnetic SIMS. However, the definitions of mass resolution for these two types of instruments are quite different. Whether it is possible to compare mass resolution and how to do such comparison is a challenge. This problem was raised officially during the 2012 ISO/TC 201 meeting at Tampa, Florida, the United States and the long‐term cooperation with ISO started afterwards. The definition of mass resolution is one of the most important and fundamental problems for mass spectrometry and should attract significant attention. Here, some detail discussions on mass resolution as well as the related experimental studies in the past few years, including the collaborations with ISO/TC 201/SC6 and SC1 are summarized. This summary covers the common problem for almost all the current existing and still used definitions of mass resolution. A reasonable new definition for mass resolution considering the peak shape or resolution function has been proposed, which has also been confirmed by using experimental studies of the mass resolution comparison between TOF and magnetic SIMS. This study lays a foundation for the future mass resolution comparisons between different mass spectrometry.